Om Bordieus reflexiva sociologi (Sociologisk Forskning, 1998)
The aim of this article is to translate some of Bourdieu’s abstract reasoning on reflexive sociology into concrete recommendations of how such a sociology can be practised. The main focus is on the relationship between practical knowledge and theoretical knowledge. Firstly, Bourdieu’s “objectified objectification“, and the fundamental conflict between practice and discourse on practice, is discussed. Secondly, the construction of the object, and Bourdieu’s dissociation from bureaucratic, administrative research categories as well as spontaneous sociological preconstructions, is analyzed. Thirdly, some of Bourdieu’s own analyses of positions, dispositions and positionings, are presented as examples of his reflexive sociology. For Bourdieu, the social is history through and through, and the main task of sociology is to discover history where it is best hidden.